Synthesis, characterization and application of two metal-organic frameworks (MOF) as a corrosion inhibitor for aluminium in a hydrochloric acid environment - Ahmed M. Wahba; Mohamed M.I. Helal (Case Studies in Chemical and Environmental Engineering)
[Cu2(EDA)2] [Cu (CN)2] 2.H2O] (MOF1) and [H2DB] [Cu4(CN)6] 2.H2O (MOF2) were synthesized and studied as a corrosion inhibitor for aluminium (Al) in 1.0 M HCl solution. The synthesis was done at room temperature via chemical method. The crystals of MOF1 and MOF2 were obtained after filtration and coating with cold H2O. The MOF precipitate was characterized by X-ray diffraction (XRD) techniques. The study aimed to evaluate the corrosion inhibition efficacy of the MOFs using mass loss, potentiodynamic polarization, and EIS electrochemical impedance techniques. Both MOF1 and MOF2 were physically adsorbed on the surface of the aluminium and acted as mixed-type inhibitors affecting metal dissolution and hydrogen evolution reactions. The inhibitors conformed to the Henry adsorption isotherm model, indicating successful adsorption on the aluminium surface. The mass loss analysis (MLA) results were obtained at (298, 308, and 318) K, and for potentiodynamic polarization (PP) and electrochemical impedance spectroscopy (EIS) results were obtained at 298 K. Increasing inhibitor doses led to increased inhibition efficiency (%IE), corresponding to 93 % for MOF2 and 91 % for MOF1 at 2.5x10−4M. The adsorption of inhibitors on Al surfaces has been calculated and discussed by a Henry isotherm. The inhibitors that were created showed great effectiveness, with a noticeable increase in their inhibitory efficiency (%IE) as the dosage was raised and the temperature was lowered. The synthesized inhibitors acted as mixed-type inhibitors based on polarization curves. The surface of Al was coated with a thin film of inhibitors, confirming the protective effect. A scanning electron microscope (SEM) technique was used to study the surface morphology of a sample of aluminium. A cell construction model and electron density map were used as theoretical calculations. The results from mass reduction, potentiodynamic polarization, and EIS electrochemical impedance techniques showed good agreement, validating the effectiveness of the MOFs as corrosion inhibitors.